Karakterisasi Rekristalit Antalgin-Fenilbutason dengan Pelarut Aseton sebagai Suatu Sistem Interaksi Fisika - Ilma Nugrahani; Slamet Ibrahim; Sundani Nurono Soewandhi; Sukmadjaja Asyarie (JURNAL ILMU KEFARMASIAN INDONESIA, 2007)
Recrystallization with acetone of antalgyne, phenylbutazone, and the mixture of binary system has been characterized. The aim of this research was looking for thermodynamic and x-ray diffraction characteristic of re-crystallite to compare with raw material characteristics. The result used to confirm validity of cool contact methods to identify physical interaction of antalgine-phenylbutazone that has been developed in the preliminary research. Recrystallites characterized by DSC and powder-XRD shows the polymorphism cases, but the co-recrystallite of binary system show the peritecticum physical interaction, similar with the physical interaction of the raw material binary system before recrystallization. Principally, the results of this investigation prove that cool contact methods by acetone could be used for identify physical interaction of antalgine-phenylbutazone.